Biosynthesis of Medium-Chain ω-Hydroxy Fatty Acids by AlkBGT of Pseudomonas putida GPo1 With Native FadL in Engineered Escherichia coli - He, Qiaofei; Bennett, George N.; San, Ka-Yiu; Wu, Hui (Frontiers in Bioengineering and Biotechnology, 2019)
Hydroxy fatty acids (HFAs) are valuable compounds that are widely used in medical, cosmetic and food fields. Production of ω-HFAs via bioconversion by engineered Escherichia coli has received lots of attention because this process is environmentally friendly. In this study, a whole-cell bio-catalysis strategy was established to synthesize medium-chain ω-HFAs based on the AlkBGT hydroxylation system from Pseudomonas putida GPo1. The effects of blocking the β-oxidation of fatty acids (FAs) and enhancing the transportation of FAs on ω-HFAs bio-production were also investigated. When fadE and fadD were deleted, the consumption of decanoic acid decreased, and the yield of ω-hydroxydecanoic acid was enhanced remarkably. Additionally, the co-expression of the FA transporter protein, FadL, played an important role in increasing the conversion rate of ω-hydroxydecanoic acid. As a result, the concentration and yield of ω-hydroxydecanoic acid in NH03(pBGT-fadL) increased to 309 mg/L and 0.86 mol/mol, respectively. This whole-cell bio-catalysis system was further applied to the biosynthesis of ω-hydroxyoctanoic acid and ω-hydroxydodecanoic acid using octanoic acid and dodecanoic acid as substrates, respectively. The concentrations of ω-hydroxyoctanoic acid and ω-hydroxydodecanoic acid reached 275.48 mg/L and 249.03 mg/L, with yields of 0.63 mol/mol and 0.56 mol/mol, respectively. This study demonstrated that the overexpression of AlkBGT coupled with native FadL is an efﬁcient strategy to synthesize medium-chain ω-HFAs from medium-chain FAs in fadE and fadD mutant E. coli strains.